2020
DOI: 10.1186/s12935-020-01227-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIR4435-2HG triggers ovarian cancer progression by regulating miR-128-3p/CKD14 axis

Abstract: Background: Accumulating studies showed that long noncoding RNAs (lncRNAs) played vital roles in cancer progression. LncRNA MIR4435-2HG was proved to act as an oncogene in various tumors. However, the underlying function of MIR4435-2HG in ovarian cancer (OC) remains unclear. Methods: The expression levels of MIR4435-2HG, miR-128-3p and cyclin-dependent kinase 14 (CDK14) were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Cell proliferation and apoptosis in OC cells were detected by 3-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…In gastric cancer, Bu et al demonstrated that AWPPH promotes cell proliferation and tumorigenesis by regulating miR-497/NTRK3 axis [22]. Recently, miR-128-3p was found to be a target of AWPPH in ovarian cancer by Zhu et al [13]. In NSCLC, Wu et al also demonstrated that AWPPH could function as an oncogenic lncRNA by regulating miR-204/CDK6 axis [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gastric cancer, Bu et al demonstrated that AWPPH promotes cell proliferation and tumorigenesis by regulating miR-497/NTRK3 axis [22]. Recently, miR-128-3p was found to be a target of AWPPH in ovarian cancer by Zhu et al [13]. In NSCLC, Wu et al also demonstrated that AWPPH could function as an oncogenic lncRNA by regulating miR-204/CDK6 axis [25].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included 19 studies were summarized in Table 1. A total of 1699 patients from 19 studies between 2016 and 2020 were included [11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. All of the included studies were conducted in China.…”
Section: Summary Of Eligible Studiesmentioning
confidence: 99%
“…Additionally, a previous study revealed that MIR4435-2HG was upregulated in gastric cancer and promotes tumor growth and metastasis via activating the Wnt/β-catenin signaling pathway (17). Several recent reports (18,19) have revealed that MIR4435-2HG was involved in the regulation of cell apoptosis. Knockdown of MIR4435-2HG in cisplatin-resistant cell line HCT116R significantly promoted cell apoptosis and restored the sensitivity to cisplatin (18).…”
Section: Introductionmentioning
confidence: 97%
“…Knockdown of MIR4435-2HG in cisplatin-resistant cell line HCT116R significantly promoted cell apoptosis and restored the sensitivity to cisplatin (18). MIR4435-2HG knockdown induced ovarian cancer cell apoptosis via the miR-128-3p/CDK14 axis (19). Therefore, targeting MIR4435-2HG using antisense oligonucleotides to induce apoptosis may be a potential advancement in cancer drug development.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA MIR4435-2 host gene (MIR4435-2HG) is located on human chromosome 2q13, and it is a proven oncogenic lncRNA that is implicated in various tumors (10). For example, MIR4435-2HG knockdown was shown to suppress the proliferation and invasion of ovarian cancer cells (11). MIR4435-2HG expression is upregulated in glioblastoma tissues and is associated with shorter overall survival in patients with glioblastoma (12).…”
Section: Introductionmentioning
confidence: 99%